Effectiveness of two sequences of Toxoplasma gondii SAG2 protein to differentiate toxoplasmosis infection stages by measuring IgG, IgA and IgM antibodies - Costa, Juan Gabriel (2016)
Here, we evaluated two Toxoplasma gondii SAG2 antigen sequences which differ in thepresence of the amino-and carboxy-terminal sequences in one of them. They were testedwith several techniques to differentiate between acute and chronic phase of toxoplasmosis:avidity assay and indirect ELISA for the detection of anti-Toxoplasma IgG, IgA and IgMantibodies. Significant differences were found between them. The best results were obtainedwith the sequence denominated SAG2c, which yielded sensitivity of 73.8% and specificity of 80.3% in the detection of IgG by ELISA. Measurement of IgA yielded 67.2% and 81.8% of sensitivity and specificity, respectively. The avidity assay yielded 100% sensitivity and 81.82% specificity. Finally, the molecular modeling and epitope predictions of the protein are developed to find the antigenic region locations, specific and nonspecific, on three-dimensional structure. This paper is the first report of promising results of SAG2 used for detecting IgA antibodies to differentiate toxoplasmosis infection stages.